PENGARUH BEBAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA APARATUR SIPIL NEGARA MELALUI ORGANIZATIONAL CITIZENSHI BEHAVIOUR (OCB) SEBAGAI VARIABEL INTERVENING (Studi pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Situbondo) - Aisy, Istiqomah Rihadatul; Tulhusnah, Lusiana; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The Agency for Personnel and Human Resources Development (BKPSDM) of Situbondo Regency is engaged as a public service in the field of staffing, education, and training in the Situbondo Regency area. As a public service, BKPSDM has the main task of coordinating and controlling the implementation of activities in the fields of personnel, education, and training. The purpose of this study was to analyze and examine the effect of workload and organizational commitment on the performance of state civil servants through organizational citizenship behavior (OCB) as an intervening variable (study at the Situbondo Regency Personnel and Human Resources Development Agency). The sampling technique used was saturated sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation – Partial Least Square (PLS-SEM) model. The results of the direct influence hypothesis test using the smart PLS 3.0 application, show that workload has a significant effect on Organizational Citizenship Behavior (OCB), Organizational Commitment has a significant effect on Organizational Citizenship Behavior (OCB), Workload has no significant effect on ASN performance, Organizational commitment has a significant effect on ASN Performance, Organizational Citizenship Behavior (OCB) has a significant effect on ASN Performance. The results of the indirect effect hypothesis test show that the workload variable on ASN Performance through Organizational Citizenship Behavior (OCB) has a significant positive effect, Organizational Commitment on ASN Performance through Organizational Citizenship Behavior (OCB) has a significant positive effect.